2012
DOI: 10.1128/mcb.00673-12
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of JAK2 by H3K9 Methyltransferase G9a in Leukemia

Abstract: Histone methylation at specific lysine residues is a crucial regulatory process in transcriptional regulation. Using chromatin immunoprecipitation with microarray technology (ChIP-chip) analysis, we found that the H3K9-me2 target gene JAK2 was an important factor during differentiation of the HL-60 promyelocytic leukemia cell line by all- trans -retinoic acid (ATRA) treatment. Here, we report that the H3K9 methyltransferase G9a negatively regulated JAK2 transcription in histone methyltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 46 publications
(43 reference statements)
0
34
0
Order By: Relevance
“…To directly assess YY1s transcriptional function at the CGI shore, we conducted sequential in vivo ChIP experiments, using antisera directed against histone modifications and proteins [namely, H3ac, 38 H3K27me3, H3K9me2, 39,40 Hdac1, Hdac2, 41 Suz12, 42 Ezh2, 39 and Ehmt2/Ehmt1 (alias G9a/ GLP), 40 which interacts with Kdm5a (alias Jarid1a)] 43 that associate and interact with YY1 to maintain transcriptional repression. Besides observing co-precipitation of YY1 with the repressive histone marks H3K9me2 and H3K27me3 at the Nr3c1 CGI shore, we also found that Ehmt2, Kdm5a, and Hdac2 co-precipitate with YY1.…”
Section: Els Induces Persistent Hypermethylation At the Cgi Shore In mentioning
confidence: 99%
“…To directly assess YY1s transcriptional function at the CGI shore, we conducted sequential in vivo ChIP experiments, using antisera directed against histone modifications and proteins [namely, H3ac, 38 H3K27me3, H3K9me2, 39,40 Hdac1, Hdac2, 41 Suz12, 42 Ezh2, 39 and Ehmt2/Ehmt1 (alias G9a/ GLP), 40 which interacts with Kdm5a (alias Jarid1a)] 43 that associate and interact with YY1 to maintain transcriptional repression. Besides observing co-precipitation of YY1 with the repressive histone marks H3K9me2 and H3K27me3 at the Nr3c1 CGI shore, we also found that Ehmt2, Kdm5a, and Hdac2 co-precipitate with YY1.…”
Section: Els Induces Persistent Hypermethylation At the Cgi Shore In mentioning
confidence: 99%
“…G9a is recruited to the JAK2 promoter to repress its transcription in a YY1-dependent manner. 43 G9a is also important in Th2 cell differentiation. CD4 + T cells from conditional knockout mice in which G9a is specifically deleted in T cells fail to differentiate into Th2 cells resulting in impaired cytokine production.…”
Section: Changing Partners and Switching Roles: From Repressor To Actmentioning
confidence: 99%
“…G9a also attenuates DNA methylation levels through the suppression of ubiquitin-like with PHD and ring finger domains 1 (UHRF1) which plays an essential function to maintain DNA methylation during HL-60 differentiation456. In HL-60 cells, G9a represses Janus kinase 2 (JAK2), the catalyst of H3Y41 phosphorylation, resulting in the inhibition of JAK2-H3Y41P-HP1α pathway-mediated leukaemogenesis78. FAD-dependent amine oxidase, lysine-specific demethylase 1 A (LSD1) is a unique protein with the ability to catalyse the demethylation of H3K4me2 and H3K9me2, and therefore act as a transcriptional repressor or activator, respectively910.…”
mentioning
confidence: 99%